Investigating the impact of changing health messages on alcohol products. (1st November 2020) - Roderique-Davies, Gareth; Davies, Nyle; Stone, Bridie; Jones, Sarah; Leeworthy, Shona; John, Bev
ABSTRACT: Background: Health warnings on alcohol labels can improve awareness regarding the risks of excessive drinking. However, the impact of labels on drinking behavior is debated in the literature. Study one aimed to examine what shoppers attend to when purchasing alcohol, whilst study two investigated the design and placement of health messages on alcohol labels. Methods: For study one, an eye-tracker device was used to measure gaze times in a mock shopping task. Participants were organized into two groups: low-risk signs (n = 5) and combined-risk signs (n = 20). For study two, the design of alcohol labels was discussed in three focus groups (n = 10). Results: In study one, products, price and brand/logo was attended to the most, with little attention or verbal references to health information. In study two, most participants approved of health warnings on alcohol labels. Participants identified a range of positive and negative elements of the current and re-designed labels as well as further harm-reduction strategies. Conclusion: Despite positive remarks about the health messages, the brief gaze times demonstrate their limited impact on alcohol purchasing. This study therefore questions the utility of health warnings on alcohol labels as a harm-reduction strategy.